Two-stage S-Band LNA Development Using Non-Simultaneous Conjugate Match Technique - Achmad Munir; Yana Taryana; Mochamad Yunus; Hardi Nusantara; Mohammad Ridwan Effendi (LPPM ITB, 2019)
This paper presents the development of a two-stage low noise amplifier (LNA) operating at the S-band frequency that is implemented using the non-simultaneous conjugate match (NSCM) technique. The motivation of this work was to solve the issue of the gain of LNAs designed using the most commonly used technique, i.e. simultaneous conjugate match (SCM), which often produce an increase of other parameter values, i.e. noise figure and voltage standing wave ratio (VSWR). Prior to hardware implementation, the circuit simulation software Advanced Design System (ADS) was applied to design the two-stage S-band LNA and to determine the desired trade-off between its parameters. The proposed two-stage S-band LNA was deployed on an Arlon DiClad527 using a bipolar junction transistor (BJT), type BFP420. Meanwhile, to achieve impedances that match the two-stage S-band LNA circuit, microstrip lines were employed at the input port, the interstage, and the output port. Experimental characterization showed that the realized two-stage S-band LNA produced a gain of 22.77 dB and a noise figure of 3.58 dB at a frequency of 3 GHz. These results were 6.1 dB lower than the simulated gain and 0.76 dB higher than the simulated noise figure respectively.